The other side of the medal: Machado de Assis as a social thinker - Souza, Patrícia Olsen de (Faculdade de Ciências e Letras - Unesp - Araraquara., 2012)
This article aims at discussing how Machado de Assis intends to revealsthrough his literature some subtleness in Brazilian society about at the end of the 19th century. Through his literature building the author undress the human behavior,showing – perspicaciously – characteristic traces of our society like the distinctionbetween “individual” and “persons”, the form veneration and the Patrimonialism thatis present in public life. Therefore, Machado makes us think about behavior traces ofour society that roots in our past and continues along time, coloring our social life andbeing present in our quotidian.